2016
DOI: 10.1371/journal.pone.0156389
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of an Educational Game for Teaching Optometry Students Basic and Applied Science

Abstract: PurposeTo compare the effectiveness of an educational board game with interactive didactic instruction for teaching optometry students elements of the core optometric curriculum.MethodsForty-two optometry students were divided into two GPA-matched groups and assigned to either 12 hours of game play (game group) or 12 hours of interactive didactic instruction (lecture group). The same material from the core optometric curriculum was delivered to both groups. Game play was accomplished via an original board game… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Also, our findings are consistent with those of [ 60 63 ] who reported a significant improvement in the knowledge level of the gamified group. In contrast, a study by Trevino et al [ 64 ] and Lee et al [ 65 ] reported that educational games had a similar impact on the knowledge level as attending an engaging, didactic lecture. Moreover, a study by Selby et al [ 66 ] reported that the interactive lecture group had better knowledge than the game group, and this was interpreted as during game playing, the students have other distractions, whereas lectures forced students to focus on facts.…”
Section: Discussionmentioning
confidence: 92%
“…Also, our findings are consistent with those of [ 60 63 ] who reported a significant improvement in the knowledge level of the gamified group. In contrast, a study by Trevino et al [ 64 ] and Lee et al [ 65 ] reported that educational games had a similar impact on the knowledge level as attending an engaging, didactic lecture. Moreover, a study by Selby et al [ 66 ] reported that the interactive lecture group had better knowledge than the game group, and this was interpreted as during game playing, the students have other distractions, whereas lectures forced students to focus on facts.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, each of these two methods of instruction can be entertaining and engaging. 15 Lambertsen et al used a virtual hospital setting to examine the effect of serious gaming in pharmacy education. "PharmaComm," the game implemented in the study allowed pharmacy students to enhance their skills and knowledge with the health of a virtual patient in a hospital environment.…”
Section: Previous Studies Involved Educational Game In Teaching In Pharmacy/health Colleges or Any Scientific Fieldmentioning
confidence: 99%